2015
DOI: 10.1002/ejoc.201500369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Dichlorinated Chondramide Derivatives

Abstract: Straightforward synthetic protocols for the synthesis of new ethyl‐substituted dichlorinated chondramides with different methyl‐substitution patterns in the polyketide fragment have been developed. The methyl groups at the ϵ‐position can be removed completely without a significant influence on the biological activity. In contrast, after removal of the α‐methyl group, a significant drop in activity is observed. This is also observed if the configuration of the α‐methyl group is inverted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…As our group is experienced in the syntheses of such peptide-polyketide conjugates [23][24][25][26], this assumption led us to develop a straightforward synthesis of doliculide, and associated derivatives, based on Matteson homologation [27][28][29], allowing late-stage variation at exactly this position [30]. In an initial modification, it was demonstrated that replacing the isopropyl group by the smaller methyl group led to almost no change in its cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…As our group is experienced in the syntheses of such peptide-polyketide conjugates [23][24][25][26], this assumption led us to develop a straightforward synthesis of doliculide, and associated derivatives, based on Matteson homologation [27][28][29], allowing late-stage variation at exactly this position [30]. In an initial modification, it was demonstrated that replacing the isopropyl group by the smaller methyl group led to almost no change in its cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning our ongoing interest into the syntheses of biological active natural products [25][26][27][28][29][30] we also focused on the synthesis of chondramide derivatives 31,32 and we developed a straightforward protocol towards the miuraenamides 33 based on a late stage modification approach. 34 This concept allowed the synthesis of a small library of miuraenamide derivatives via aldol reaction at the C-terminal position of a glycine containing cyclodepsipeptide (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…During our previous studies on the closely related chondramides, we observed that incorporation of halogens into the C ‐terminal aromatic amino acid had a positive effect on the biological activity of these compounds, so we decided to investigate the influence of halogens on the aryl ketone also in this case (Table ). Although one might expect a higher reactivity of the halogenated benzaldehydes, we observed a significantly slower reaction.…”
Section: Resultsmentioning
confidence: 99%